COMPARATIVE ADVANTAGES OF APPLYING AN INNOVATIVE SUBSURFACE IRRIGATION SYSTEM IN AGRICULTURE OF THE REPUBLIC OF SERBIA–ECONOMIC ASPECTS - Nataša KLJAJIĆ; Jonel SUBIĆ; Vesna PARAUŠIĆ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the research in this paper is to confirm the economic justification of the application of innovative subsurface irrigation “Agrokapilaris”. In the introduction, an overview of irrigated areas in the Republic of Serbia is given, from which it is clear that irrigation was applied in 2022 by 4.6% more compared to the previous year and that this is a small but at least some progress, with a tendency to further increase areas with irrigation systems. Also, the key features of the innovative subsurface irrigation are given. The innovative subsurface irrigation has been used for some time on plots in Serbia. In this paper authors examine further development and economic profitability of this irrigation model, on the example of its application in the plastic greenhouse production of vegetables on the agricultural property of the Secondary Agricultural and Chemical School in Obrenovac, Serbia. The assessments of the economic effectiveness of investments in this type of irrigation system in plastic greenhouse vegetable production, on an area of 0.5 ha, showed, based on static calculations that the investment will succeed in 4.02 years. According to the dynamic calculation, the investment project will succeed in 4.26 years, which clearly shows the quick return of the invested funds in this type of irrigation system, that is, justified investments.